The Social Science Learning Effectivity in a Post-Pandemic through Active Learning Method at Al-Ma’arif Junior High School in Jombang 2022 - Bashith, Abdul; Asnawan, Asnawan (Didaktika Religia, 2022)
Since Covid-19 was declared a pandemic by WHO, almost all activities from all aspects of life had problems, and so as in education, especially in the learning aspect. Indonesian learning process faces several changes that require educational institutions to be creative to minimize the impact of the Covid-19 pandemic. Many adjustments are learning carried out by educational institutions, which in its adjustment take into account the conditions and situations to be experienced. That is one of the effective methods is the implementation of active learning. This paper intends to know the kinds of active learning methods that can be implemented, the active learning process, and the results of active learning itself. The subject of this paper is Al-Ma’arif Junior High which is located in Jombang-Jember. This paper then concludes that: 1) the active learning methods that are implemented are group discussion, social observation, inductive learning, contextual, presentation, problem-solving, and demonstration; 2) the active learning process consists of three stages, namely planning, implementation and evaluation; 3) the results of this method is developing students’ ability on cognitive, affective and psychomotor.